2021
DOI: 10.5115/acb.21.081
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of lacrimal sac fossa affecting success rate in endoscopic and external dacryocystorhinostomy surgery in Mongolians

Abstract: To study the affect of anatomical variance of lacrimal sac fossa on dacryocystorhinostomies (DCR) performed by the traditional external (EX-DCR) approach or an endoscopic (EN-DCR) endonasal approach. A total of 292 consecutive cases with primary nasolacrimal obstruction underwent DCR surgery. Orbital computed tomography scan was used to measure lacrimal sac fossa and other related structures and Lac-Q questionnaire was used to compare surgery result. Maxillary portion of lacrimal sac fossa is thicker in failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Japanese: upper, 4.6 mm; lower, 6.30 mm) (10,11). Purevdorj et al (2021) reported that thicker maxillary bone at the lacrimal sac fossa might lead to decreased success rates for endoscopic and external DCR interventions (23). In this study, midpoint thickness was higher at upper and lower planes in males.…”
Section: Discussionmentioning
confidence: 54%
“…Japanese: upper, 4.6 mm; lower, 6.30 mm) (10,11). Purevdorj et al (2021) reported that thicker maxillary bone at the lacrimal sac fossa might lead to decreased success rates for endoscopic and external DCR interventions (23). In this study, midpoint thickness was higher at upper and lower planes in males.…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have evaluated the lacrimal sac fossa length and morphology using orbital CT, suggesting a potentially consistent anatomical reference for endo DCR/CDCR including opercula of the middle turbinate and the uncinate process. 12,13,22 Furthermore, the lacrimal sac fossa bone should be removed to its complete depth to ensure proper ostium formation. Therefore, a comprehensive understanding of the anatomy of the lacrimal sac fossa may influence the success rate in Endo DCR/CDCR.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative orbital CT assessment can be a valuable tool to achieve a better understanding of the anatomy of main endonasal and nasolacrimal system landmarks, leading to safe and proper removal of the nasal mucosa and creation of sufficiently sized ostium and correctly placed osteotomy. Previous studies have evaluated the lacrimal sac fossa length and morphology using orbital CT, suggesting a potentially consistent anatomical reference for endo DCR/CDCR including opercula of the middle turbinate and the uncinate process 12,13,22 . Furthermore, the lacrimal sac fossa bone should be removed to its complete depth to ensure proper ostium formation.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showing that there is a variability in the LSF morphology and intranasal space between the different ethnic groups age and sex [7][8][9][10]. Generally, the lacrimal bone proportion of the lacrimal fossa appears to be higher in Indians, compared to other racial groups such as the Caucasians, Koreans, or black African [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%